PERHITUNGAN PREMI ASURANSI JIWA SEUMUR HIDUP, ASURANSI JIWA BERJANGKA, SERTA ASURANSI JIWA DWIGUNA TERHADAP TOLAK UKUR UMUR YANG PALING OPTIMAL UNTUK BERGABUNG ASURANSI JIWA - Mhd Ghazy Arkan; Indah Cantika Balqis; Muhammad Fakhrurrozy Siregar; Indra Sembaya Timanta Barus (LPPM Universitas Bina Bangsa, 2024)
Determining the optimal age to enter life insurance is a crucial decision that affects benefits and premiums. The study evaluated comparisons between term life insurance, whole life insurance, and dual-purpose life insurance to identify the most favorable lifespan for participants. Through the analysis of single premiums and co-benefits, the study provides insight into insurance options that suit individual needs at different stages of life. The results can guide policyholders in taking the right decisions related to life insurance, considering financial aspects and long-term benefits